Loan Loss Provisioning Practices of Chinese Banks - ZHANG, TIANXIN (2017)
This paper intends to investigate Chinese banks loan loss provisioning behaviour, with an unbalanced data of 128 banks from period of 2007-2016. We assume that there exists relationship of loan loss provisions with capital management, income smoothing, cyclicality, X-Efficiency and Z score. We adopt Stochastic Frontier Analysis to estimate X-Efficiency and Generalized Method of Moments estimator to capture the correlations between LLP and independent variables consisted of bank specific and macroeconomic factors. As a result, we find that LLP have been utilised to manipulate capital ratios. Loan loss provisions also found to be countercyclical with GDP growth variable but no evidence found that unemployment rate has cyclical effect on LLP. There results no evidence support for the hypothesis of income smoothing, X-Efficiency and Z score, which indicates there is no reliable correlation between LLP and these variables in Chinese banking sector.